Pengendalian Persediaan Bahan Baku menggunakan Metode Min-Max Stock pada Perusahaan Konveksi Gober Indo - Abdus Salam; Mujiburrahman Mujiburrahman (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2018)
Inventory of raw materials is the company's current assets that are used for production activities on the company continuously. Convection companies need to control inventory because it influences the smooth production process. Lack of inventory can result in disruption of the production process. While excess inventory can cause waste because companies need to spend more capital on inventory costs. The purpose of this study is to find out whether CV. Gober Indo Group has properly controlled the inventory of raw materials. The raw material inventory control method used in this study is the min-max stock method. This method determines how many safety supplies, minimum inventory, maximum inventory, and order quantity. After doing research, CV. Gober Indo Group has excess inventory of raw materials. The amount of inventory controlled by using the min-max stock method produces results that are more efficient when compared to the amount of the company's final inventory.